Architekten- und Designer-Ehepaar Jacques und Jacqueline Groag Zwei vergessene Künstler der Wiener Moderne - Prokop, Ursula (2005)
This manuscript is based on the results of a research project (No. 7726), carried out at the Institute for the History of Art (University of Vienna) under the direction of Professor Dr. Peter Haiko, and sponsored by the Jubilee Funds of the Austrian National Bank. The artists Jacques Groag (b. Olomouc, February 5, 1892, d. London, January 26, 1962) and his wife Jacqueline (née Hilde Blumberger, b.Prague, April 6, 1903, d. London, January 13, 1986) belong to those representatives of the Viennese Modernists between the two World Wars who are now forgotten, due to the fact that, being Jews, they were forced to emigrate in 1938. In the early phase of his career Jacques Groag worked as an assistant and executing architect for Adolf Loos (Moller house, 1927) and Ludwig Wittgenstein (Wittgenstein house, 1928) and co-operated with the interior designers Friedl Dicker and Franz Singer (Heller tennis club house, 1928). After that, in independent practice he realized a considerable number of remarkable architectural projects in Vienna and native Moravia (now Czech Republic), among others a pair of semi-detached houses at the Werkbundsiedlung, a house for the actress Paula Wessely, a country house for the industrialist Otto Eisler, several houses for other private clients, but also industrial buildings. At this time he was regarded as one of the most important followers of Adolf Loos. He also enjoyed remarkable success as a designer of interiors, and was befriended to many Viennese artists such as the painters Sergius Pauser and Josef Dobrowsky, the sculptor Georg Ehrlich and the photographer Trude Fleischmann. His wife Jacqueline, a student of Franz Cizek and Josef Hoffmann at the Wiener Kunstgewerbeschule, between the wars was active as a designer of textiles for the Wiener Werkstätte and for fashion houses in Paris. After the couple's emigration to England in 1939 Jacques Groag could only find commissions as a designer of interiors and furniture, but found no opportunity to realize architectural projects. As a team, Jacques and Jacqueline made important contributions to prominent exhibitions on British design in the post-war period. Jacqueline, who outlived her husband for more than twenty years, continued her career as a successful textile designer until her late age.